[PP.16.04] AMBULATORY BLOOD PRESSURE MONITORING PROFILE IN A CROSS-SECTIONAL ANALYSIS OF A LARGE DATABASE OF REAL OR SUSPECTED HYPERTENSIVE PATIENTS. (September 2017) - Polonia, J.; Araujo, S.; Rouxinol-Dias, A.; Silva, J.
Abstract : Objective: To evaluate ambulatory blood pressure monitoring (ABPM) parameters in a broad sample of hypertensive patients. Design and method: A total of 26.304 individual ABPM were analyzed corresponding to real or suspected hypertensive patients observed in or referred to a ESH excellence center 1995–2015). Mean blood pressures at daytime (dayBP), nighttime (nightBP), 24-hour period (24hBP) and morning surge (Morn BP) were measured. Circadian patterns were defined facing nocturnal systolic BP fall: extreme dipper (ED> 20%), dipper (D10%-20%), non-dipper /riser (NDR) (< 10% or nocturnal BP increase). Results: Population was 52% female, ageing 58+15 years, BMI 27+5 Kg/m 2 . Under the criteria of ABPM normalcy, 16.9% were normotensives (NT), 50.5% were untreated or uncontrolled hypertensives (noncHT) and 32.6% were controlled hypertensives (cHT) irrespective of casual BP. In the group of NT 45.1% had casual BP > = 140/90 mm Hg (white coat HT). In group of cHT 51.7% had casual BP > = 140/90 mm Hg (false uncontrolled/resistant HT). In group of noncHT 16.1% had casual BP < 140/90 mmHg (masked hypertension). The 24hBP, dayBPe, and nightBPe values were lower than those obtained at the office regardless of normotension/hypertension status. Age was the most important determinant of NDR. The % of NDR was higher in obese (BMI>30Kg/m 2 ) than in non-obese (56.5 v 43.5%, p < .000), higher in noncHT than in cHT and NT (60.7 v 24.3 v 15.0%, p < .000), higher in age >65yrs and 40–65 years than in <40 years (46.4 v 42.3 v 11.2%, p < .000) regardless of normotensive or hypertensive status. Nocturnal SBP fall (in %) was higher in NT v cHT v noncHT (11.3+6.7, v 10.6+7.7 v 9.9+8.0%, p < .000). Morn BP was lower in NT v cHT v noncHT (22+13 v 23+16 v 25+19, p < .000). Conclusions: We confirm the presence of a marked discrepancy between casual and ABPM values, with a high percentage of occurrences of abnormal circadian BP rhythm and of white coat, masked and false uncontrolled hypertension. Also the rates of ABPM control are more than double of that of casual BP. The study reinforces the importance of ABPM in the clinical evaluation of the hypertensive status.